Implementation of Project Instruments to Measure Creativity in History Learning Using Canva Platform for Grade X and XI at SMAN 4 Yogyakarta - Lia Januarsih; Dhorika Hasna; Yohanes Elfanius; Fahruddin (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
The aim of this research is to determine the extent of students' creativity in history learning, specifically in the subject of History (Specialization), at SMAN 4 Yogyakarta, through the utilization of technology such as Canva. This research adopts a Research and Development (R&D) approach. The analysis of project-based creativity assessment that will be examined includes the validity test, reliability test, and expert judgment, using Microsoft Excel and SPSS 22.0 as supporting tools. The research findings indicate that the project-based creativity assessment was conducted with 72 data from a total of 144 students in grade 10 and 11. The students assessed each other, and then the teachers evaluated the students. The validity level (exceeding the critical value) of the assessment of creativity, as evaluated among students, was deemed valid in terms of planning, implementation, and reporting aspects. However, in the evaluation conducted by the teachers, the planning aspect was considered invalid, while the implementation and reporting aspects were valid. The inter-rater reliability of the data among students was 0.693, and among teachers was 0.584, indicating reliability. The expert judgment test, conducted through a questionnaire answered by experts regarding the statements, indicated that the instrument was deemed suitable for use. The analysis of the project assessment results, in measuring creativity through the utilization of technology with Canva, is highly recommended as it can enhance creativity in history.